Molecular detection of Vibrio cholerae from human stool collected from SK Hospital, Mymensingh, and their antibiogram - Zereen, Farah; Akter, Soudiya; Sobur, Md Abdus; Hossain, Muhammad Tofazzal; Rahman, Md Tanvir (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: Vibrio spp., particularly, Vibrio cholerae is a major etiology of diarrhea in humans worldwide. In this study, we isolated and identified V. cholerae from the human stool of suspected cases along with antibiogram. Materials and Methods: In total, 25 stool samples from cholera suspected patients were analyzed. Isolation and molecular detection of Vibrio species were performed based on staining, motility, cultural and biochemical characteristics followed by polymerase chain reaction (PCR) using groEL gene-specific primers. Results: Among the 25 samples, seven showed growth of yellow color colonies on Thiosulfate- Citrate-Bile salts-Sucrose agar plates. The isolates were Gram-negative, curved shaped, and motile. Biochemically, they were found positive for indole and Methyl Red tests and negative for Voges–Proskauer test. Out of the seven positive samples, only three isolates were confirmed as Vibrio spp. using genus-specific primers. Subsequently, these three isolates were confirmed as V. cholerae by PCR using V. cholerae groEL gene-specific primers. Antibiotic sensitivity test revealed these three isolates as highly sensitive to azithromycin, chloramphenicol, gentamicin, and norfloxacillin while resistant to streptomycin, tetracycline, and oxacillin. Conclusion: Vibrio cholerae were isolated from the stool of diarrheic human patients and confirmed by PCR targeting the groEL gene. The isolates were found resistant to streptomycin, tetracycline and oxacillin, and need further characterization to reveal the molecular basis of their origin and resistance. J. Adv. Vet. Anim. Res., 6(4): 451-455, December 2019